Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/humrep/dew196
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal paracetamol exposure is associated with shorter anogenital distance in male infants

Abstract: STUDY QUESTIONWhat is the relationship between maternal paracetamol intake during the masculinisation programming window (MPW, 8–14 weeks of gestation) and male infant anogenital distance (AGD), a biomarker for androgen action during the MPW?SUMMARY ANSWERIntrauterine paracetamol exposure during 8–14 weeks of gestation is associated with shorter AGD from birth to 24 months of age.WHAT IS ALREADY KNOWNThe increasing prevalence of male reproductive disorders may reflect environmental influences on foetal testicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 39 publications
3
55
2
Order By: Relevance
“…Thus, there is a significant male-female difference in AGD by 11-13 weeks' gestation (54), which is fully developed by 17-20 weeks (26,54). Moreover, fetal exposure to painkillers, which has been shown to suppress testosterone production by the fetal human testis (55), is associated with reduced AGD in boys (56,57), and this may be restricted to exposures during 8-14 weeks' gestation (56).…”
Section: )mentioning
confidence: 99%
“…Thus, there is a significant male-female difference in AGD by 11-13 weeks' gestation (54), which is fully developed by 17-20 weeks (26,54). Moreover, fetal exposure to painkillers, which has been shown to suppress testosterone production by the fetal human testis (55), is associated with reduced AGD in boys (56,57), and this may be restricted to exposures during 8-14 weeks' gestation (56).…”
Section: )mentioning
confidence: 99%
“…Specifically, epidemiological studies published over the past few years have suggested that prenatal exposure to antiandrogenic compounds, such as phthalates, dioxins, and bisphenol A, may be associated with shortened AGD in children (Bustamante‐Montes et al ., ; Miao et al ., ; Papadopoulou et al ., ; Swan, ; Swan et al ., ; Vafeiadi et al ., ). More recently, a shorter AGD has also been associated with the intake of certain analgesics during pregnancy (Fisher et al ., ; Lind et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…However, these results do not show a paracetamol-only induced effect and this may highlight the importance of exposure to ‘mixtures’ potentially resulting in additive effects which may be more representative of analgesic intake during pregnancy 36. A similar study (n=434 male infants) reported an association between paracetamol exposure and reduced AGD from birth to 2 years which was independent of body size37 and interestingly, this association was limited to paracetamol exposure during the proposed human MPW (ie, first trimester). Importantly, all of the above epidemiological studies are based on self-reporting of analgesic use, determined in most cases by the use of retrospective questionnaires.…”
Section: Effects Of Exposure To Paracetamol On Male Reproductive Healthmentioning
confidence: 66%